'SIB': what does it really mean? A theoretical approach to understanding social impact bonds. Issue 2 (17th February 2022) - Pastore, Lavinia; Corvo, Luigi
IMPACT: SIBs are a relatively new research field. Building on the contributions to the 2020 theme issue of Public Money & Management on SIBs, this paper helps policy-makers to be more aware of the potential and downsides of SIBs. The authors provide policy-makers and public sector managers with the tools to assess a SIB design.